As encruzilhadas da autogestão: imaginário e simbólico nas empresas assumidas por trabalhadores: uma análise de empreendimentos da economia solidária - Meira, Fabio Bittencourt (2009)
Solidarity Economics (SE) is the background of this research. The intended approach is centered on the organizational perspective. The problem of research is defined by the lack of the interrogation on organizations within the theoretical construct of SE. The aim of the research is to comprehend organizational phenomena created in the SE realm. The research is focused on firms assumed by workers (FAW), which are conventional firms that have sunk in a crisis or gone bankrupt, being assumed by ex-employees. The question of research asks the way by which workers reinvent the management of the assumed enterprises, the changes dealt with and transformations undertaken on inherited management practices. The imaginary and symbolic are the analytical categories used to access the reality of these organizations. Articulated with the approach of minority groups they allow us to apprehend the dynamics of the changes carried on, the sense of the new practices and the track followed by the group of workers while constructing them. Two case studies illustrate the dynamics of the changes managed.